Party for one : perfectly portioned recipes just for you - Dawson, Meredith; Stephenson, Emily (Union Square and Co, 2026)
"If you're picking up this book, chances are you think cooking is one of the ultimate acts of care -- both for others and for yourself. But why are most recipes meant to serve four to six people -- or more? When you're cooking for yourself, all that matters is you, especially when you've got places to be, things to do, and a craving to satisfy. Cooking for one often means scaling down ingredients and adjusting cooking times: it can drive you crazy. Sometimes, one is all you want. In her debut cookbook, Meredith Dawson invites you to lean in to being alone (because being alone is great!) and enjoy single-serving dishes designed to indulge whatever your mood might be in any given moment. Because your opinion is the only one that matters!"--